Hepatitis B virus related stigma among Chinese living in mainland China: a scoping review. Issue 8 (14th September 2022) - Jin, Defeng; Treloar, Carla; Brener, Loren
ABSTRACT: Stigma related to hepatitis B virus (HBV) has a detrimental impact on health outcomes of people living with HBV. A scoping review of published peer-reviewed articles focused on the Chinese population in mainland China published between 2010 and 2019 was undertaken. This review consists of five stages: identifying the research question, identifying relevant literature, study selection, charting the data, and collating, summarizing and reporting the results. Articles in Chinese were identified from the collection of Core Journals in the database of CNKI (China Academic Journals Full-text Database). Publications in English were identified in Global Health, Scopus, PsycINFO, Proquest and Web of Science. Forty-five peer-reviewed articles were selected for inclusion. Most studies under review focused on negative individual attitude and discrimination against people living with HBV (PLHBV) in employment, education, community and healthcare settings. There is limited information on lived experiences of those living with HBV and how they manage this stigma. The reviewed studies provide evidence for the existence of different forms of HBV-related stigma in a variety of settings. Knowledge about HBV and the level of education of research participants were the most frequently identified factors related to this stigma. These findings are useful to support HBV responses in China and countries with migration from China.